The Role of Service Quality toward Open University Website on The Level of Student Satisfaction - Wildoms Sahusilawane; Lilian Sarah Hiariey (Journal of Education and Learning (EduLearn), 2016)
The purpose of this research is to find out the impact of variable service useability, information quality, and service interaction quality to students’ satisfaction in applying open-university website. The population is non-primary education students on two district areas, that is, West Ceram and Southeast Moluccas including thirty (30) respondents. This research uses purposive sampling as research method in which it fulfils total of thirty (30) respondents. The questionnaire was tested by using reliability test and validity test. Then, it was continued with classic assumption test contained of multicollinearity test, normality test, and heteroskedasticity test. After that, there was hypothesis test and discussion. The results of research in partial showed that variable service useability and service interaction quality have given positive and significant impact to students’ level of satisfaction. While, service information quality did not give significant impact to students’ level of satisfaction. Results of research conducted jointly from three variables Usability, Information Quality and Service Interaction positive and significant impact on the level of student satisfaction results of research conducted jointly from three variables Usability, Information Quality and Service Interaction positive and significant impact on the level of student satisfaction that Fhitung = 39.246 with a significance of 0.000 less than 0.5.